TED Talks as a Listening Resource in the EFL College Classroom - Al-Jarf, Reima (International Journal of Language and Literary Studies, 2021)
The article proposes a model for integrating TED Talks (TTs) in EFL college listening practice. It shows instructors where TTs can be located, gives reasons for using TTs, criteria for selecting TTs, the listening skills that can be developed, and an instructional strategy. TTs provide a variety of real-life themes, speakers, motivation, and inspiration. They save instructors’ time and effort as they are available on You Tube, mobile apps or in the TED website. In selecting TTs, the instructor should take into consideration the students' interests, difficulty level of the TT language and content, its length in minutes, and speed and accent of the speaker. Before watching a TT, she posts the title of the TT on an LMS or social media platform. She sets goals for listening and gives pre-questions to help the students comprehend the TT content. The students view the TTs on their smart phones in the classroom or at home; individually, in pair, or small groups; synchronously or asynchronously. While listening, the students take notes, and answer the questions. After listening, they discuss their answers. The instructor serves as a facilitator. She gives feedback, encouragement, and help with difficulties. Further recommendations for enhancing EFL college students’ listening skills and for extending the use of TTs to interpreting courses are given.